2013
DOI: 10.1007/s10661-013-3454-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistant E. coli in surface water and groundwater in dairy operations in Northern California

Abstract: Generic Escherichia coli was isolated from surface water and groundwater samples from two dairies in Northern California and tested for susceptibility to antibiotics. Surface samples were collected from flush water, lagoon water, and manure solids, and groundwater samples were collected from monitoring wells. Although E. coli was ubiquitous in surface samples with concentrations ranging from several hundred thousand to over a million colony-forming units per 100 mL of surface water or per gram of surface solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 27 publications
3
32
0
1
Order By: Relevance
“…The findings of present study is supported by Li et al (2014) and Blaak et al (2014) who stated almost similar prevalence of E. coli in dairy waste water and recreational water. E. coli, isolated from hospital effluent showed highest resistance (ranging from 66% to 100%) against amoxicillin, cephalothin, tetracycline, sulphamethoxazole-trimethoprim, ceftriaxone, nalidixic acid and enrofloxacin.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings of present study is supported by Li et al (2014) and Blaak et al (2014) who stated almost similar prevalence of E. coli in dairy waste water and recreational water. E. coli, isolated from hospital effluent showed highest resistance (ranging from 66% to 100%) against amoxicillin, cephalothin, tetracycline, sulphamethoxazole-trimethoprim, ceftriaxone, nalidixic acid and enrofloxacin.…”
Section: Discussionsupporting
confidence: 87%
“…The study revealed that the percentage of E. coli in untreated hospital effluent was 100%. Many of the previous studies indicated that the prevalence of E. coli varies widely based on type of environmental samples and it was ranging from 44% to 100% in different environmental samples such as sewage, sludge, recreational water, dairy surface water and ground water (Anastasi et al, 2010;Li et al, 2014;Blaak et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli strains isolated from surface and ground water in Northern California showed resistance towards tetracyclines, chloramphenicol, ampicillin and amoxicillin [15].…”
Section: Ecotoxicity Of Pharmaceuticalsmentioning
confidence: 99%
“…However, widespread application of antibiotics in human and veterinary medicine has led to the emergence, selection, and dissemination of antibiotic resistant bacteria and genes encoding for antibiotic resistance in different environmental compartments such as surface water (Zhang et al, 2015;Stoll et al, 2012), groundwater (Li et al, 2014), drinking water (Schwartz et al, 2003;Guo et al, 2014) and sediments (Rosas et al, 2015) throughout the world. Antibiotic resistance genes (ARGs) and virulence genes (VGs) are emerging environmental contaminants (Pruden et al, 2006;Haack et al, 2009).…”
Section: Introductionmentioning
confidence: 99%